Frozen - Buck, Chris; Lee, Jennifer (Screenwriter); Bell, Kristen, 1980-; Tudyk, Alan; Menzel, Idina; Beck, Christophe, 1972-; Andersen, H. C. (Hans Christian), 1805-1875 (Burbank, CA : Walt Disney Studios Home Entertainment, 2014)
A princess sets out on a journey to find another missing princess and save the kingdom from eternal winter.
DVD, NTSC, Region 1; widescreen (2.24:1 aspect ratio) presentation; Dolby Digital 5.1; Dolby Digital 2.0.
In English, dubbed French, or dubbed Spanish; optional subtitles in French and Spanish.
Open-captioned in English for the deaf and hard of hearing.
Voices: Kristen Bell, Alan Tudyk, Idina Menzel, Josh Gad, Jonathan Groff.
Camera, Scott Beattie, Mohit Kallianpur; editor, Jeff Draheim; music, Christophe Beck.
Videodisc release of the motion picture produced in 2013.
Keywords: Andersen, H. C. -- 1805-1875 -- Film adaptations; Princesses -- Drama; Winter -- Drama; Missing persons -- Drama; Video recordings for hard of hearing people; Comedy films; Musical films; Action and adventure films; Fantasy films; Computer animation films; Animated films; Film adaptations; Feature films